Pengaruh Iklim dan Komunikasi Terhadap Semangat Kerja Pada Dinas Perpustakaan dan Kearsipan Kabupaten Empat Lawang (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
The study aims to identify the impact of the work climate and communication on the occupational spirit of the library service and archivist empat lawang district. The number of samples used in the study is 32 library and archive employees empat lawang district using census methods, the method for collecting data used in this study is a library study. Then the field study of interviews, observations, that deals with the problems being studied for clear data. The method of analysis used in this study is qualitative and quantitative analysis that is data analysis using a linear regression formula with a equations . Based on research done on library and archive services empat lawang district, and analysis of the effects of the working climate and communication on the spirit of work might be drawn the following: tests is shown there isa significant influence on employment climate variables (X1) on employment spirits while communication variables have no bearing on the occupational spirit of the library and archive service empat lawang district. Test f is found ina linear relationship between the work climate (X1) and communication (X2) together or simultaneously have a significant impact on the spirit of work for the library services and archive service empat lawang district (Y). Of the two factors, the work climate and communication that have the most dominant influence on the spirit of work for the library and archive service empat lawang district is the work climate.